Teaching English as a foreign language to rural education students - López-Obregón, Juan Carlos; Rodas-Auquilla, Tania Alexandra (IUSTITIA SOCIALIS, 2022)
The purpose of this study was to focus on the perspectives, problems, and suggestions of rural EFL teachers while teaching English to students in rural areas. This cross-sectional study aimed to identify the factors affecting students' motivation to learn English in the rural area of Ponce Enriquez. The technique used was a survey. The primary outcome was to understand from the students' perceptions the elements that impact the lack of motivation and the value of learning a foreign language. In addition, this study found that the main obstacles faced by EFL teachers in rural locations were students' low enthusiasm for learning English. As a result, the participants made joint recommendations to English teachers in rural areas.